PENGEMBANGAN ASPEK NON VERBAL PERILAKU ASERTIF DENGAN ASSERTIVE TRAINING - Rara Ririn Budi Utaminingtyas (Admisi dan Bisnis, 2019)
This study aim at to know that assertive training effective to develop non verbal aspect from assertive behavior.This Quasi experiment’s  pretest-posttest one control group design, Participants were 45 polytechnic students. The members of the experimentsand the control groups were randomly chosen. The treatment assertive training were given to the experiments group 0f 23 students. The 22 students did not experience the treatments. The data were collected  by questionnaires and doing observation. Different tes (t test) was employed to analise the data. It is found that  no difference non verbal aspect assertive behavior  between experiments and control groups in pretest situation. There is difference significantly between pretest and   posttest for non verbal aspect assertive behavior.There is difference significantly for non verbal aspect assertive behavior between eksperiment and control groups.. The finding imply that assertive training effective to develop non verbal aspects assertive behavior